Characteristics and clinical outcomes of hip fracture patients during the first lockdown of COVID-19, lessons learnt: A retrospective cohort analysis. Issue 12 (December 2021) - Iyengar, Karthikeyan P; Khatir, Mohammed; Mohamed, Muyed Kamal Awadalla; Kariya, Ankur D; Jain, Vijay Kumar; Sangani, Chetan; Adam, Riad F; Suraliwala, Khushroo
Background: The management of hip fracture patients has been challenging across the UK in the wake of emergency coronavirus disease 2019 guidelines. Aims: This retrospective, observational cohort study analyses the impact of the first lockdown during the early part of the coronavirus disease 2019 pandemic on the management of hip fracture patients at a district general hospital in the UK. Methods: Comparative analysis to assess hip fracture patients treated at this Trust between 1 April to 31 May 2019 and 1 April to 31 May 2020 was undertaken. The primary outcome measures appraised were 30 and 60-day mortality and the secondary outcome measure included time to surgery. Results: There was a higher 30 and 60-day mortality rate in the first lockdown period at 8.1% and 13.5%, respectively, compared to 1.96% and 5.88% in 2019. A significantly lower proportion of hip fracture patients at 59.46% were operated within the 36h target time frame during the first lockdown. Conclusion: In our Trust, hip fractures were treated as obligatory injuries. However, the mortality was higher in the 2020 cohort with a significant reduction in patients achieving the recommended '36 hours' time to surgery target and accruement of Best Practice Tariff. Enhanced infection control strategies have prepared us for the future.